Securitizing the technoplatformized City: How delivery workers construct urban safe spaces in Chile's gig economy - Iván Ojeda-Pereira (Digital Geography and Society)
This article examines the intersection of digital delivery platforms, urban construction, and worker agency in Antofagasta, northern Chile. Drawing on qualitative ethnographic research, it explores how delivery platform workers navigate, appropriate, and symbolically transform urban space within the constraints of the gig economy. The study foregrounds the spatial and affective practice of socio-urban securitization through the creation of informal “safe spaces,” exemplified by a kiosk that functions simultaneously as a resting point, a site of socialization, and a node of symbolic territorialization. Far from being merely functional, these spaces carry emotional and collective significance, enabling survival and community-building amidst structural precarity. By centring the lived experiences of migrant workers, the article contributes to emerging debates on the socio-technical and territorial dimensions of platform labour. It argues for expanding research agendas to include spatial justice and territorial politics in gig economies, emphasizing how digital platforms and worker agency co-produce the urban. The findings reveal how delivery workers negotiate layered risks—personal, work-related, and institutional—while constructing forms of resilience in the face of economic insecurity and spatial exclusion. This research advances a critical lens on the evolving entanglements between platforms, cities, and labour, proposing new directions for studying socio-technical territorialities.